Hubungan Antara Pemberian Makanan Tambahan Lokal Berbahan Dasar Daging Ayam dengan Perubahan Status Gizi Balita di Desa Sananrejo Turen - Ulva Annas; Tut Rahyani A. W (Lembaga Pengembangan Kinerja Dosen, 2025)
The nutritional status of toddlers is a key indicator in assessing the quality of child growth and development, which is strongly influenced by mothers' knowledge and attitudes toward balanced nutrition. A lack of understanding regarding proper nutritional intake may lead to slow weight gain and an increased risk of undernutrition in toddlers. This study aims to analyze the relationship between the provision of local supplementary food (PMT) made from chicken meat and changes in the nutritional status of toddlers in Sananrejo Village, Turen. The research used a descriptive quantitative design with a comparative approach. A total of 30 mothers with toddlers participated as respondents through total sampling. Data were collected using questionnaires and weight measurements of children before and after the intervention, and analyzed using an Independent T-Test. The results showed a significant difference (p < 0.05) in toddlers' weight gain between the intervention and control groups. Toddlers who received high-quality PMT based on chicken meat, along with nutrition education, showed better improvements in nutritional status. Thus, it can be concluded that good maternal knowledge and attitudes, as well as local PMT interventions based on animal protein, effectively improve toddler nutritional status. This strategy is feasible for implementation in community-based nutrition programs at the village level.